2011
DOI: 10.1007/s00464-011-1896-6
|View full text |Cite
|
Sign up to set email alerts
|

Advance in diagnosis and treatment of small bowel tumors: a single-center report

Abstract: New development of different endoscopic approaches to the small bowel has led to reach an earlier diagnosis of small-bowel tumors and a preoperative diagnosis with consequent minimally invasive surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This is in concordance with the findings of others 3 , who also explained that the initially sampled tissue can be superficial to the targeted lesion. Additionally, 100 % agreement regarding histological and laparoscopically resected specimens was shown for DBE 39 , with the fact taken into consideration that in five cases of suspected GIST, biopsies were not obtained. Afterward, four GISTs and one gastrointestinal autonomic tumor (GANT) were further confirmed surgically.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is in concordance with the findings of others 3 , who also explained that the initially sampled tissue can be superficial to the targeted lesion. Additionally, 100 % agreement regarding histological and laparoscopically resected specimens was shown for DBE 39 , with the fact taken into consideration that in five cases of suspected GIST, biopsies were not obtained. Afterward, four GISTs and one gastrointestinal autonomic tumor (GANT) were further confirmed surgically.…”
Section: Discussionmentioning
confidence: 88%
“…Taking into consideration studies that provided surgical specimen histopathological data 32 39 40 , we demonstrated that in 80 % of the DBE biopsies that missed the diagnosis, the lesions were of subepithelial origin. The misdiagnosed lesions included three gastrointestinal stromal tumors (GISTs), one leiomyoma, and one adenocarcinoma, demonstrating a low histological diagnostic yield for DBE in subepithelial tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, the diagnosis of SBMLs is difficult owing to their low incidence, nonspe-Manuscript submitted October 29, 2022, accepted December 8, 2022 Published online December 18, 2022 cific clinical presentation, and location beyond the reach of standard endoscopic evaluation [1,3]. Indeed, up until the past two decades, these lesions were typically only diagnosed with surgical laparotomy [4,5]. Since its approval in 2001, video capsule endoscopy (VCE) has played a significant role in detecting SBMLs in patients presenting with a variety of complaints ranging from occult GI bleeding to abdominal pain and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Since its approval in 2001, video capsule endoscopy (VCE) has played a significant role in detecting SBMLs in patients presenting with a variety of complaints ranging from occult GI bleeding to abdominal pain and weight loss. As it typically allows for inspection of the entire small bowel and has a diagnostic yield as high as 91% for detecting SBMLs, the incidence of detected SBMLs increased from 11.8 cases per million in 1973 to 22.7 cases per million in 2004 [3][4][5][6][7][8][9]. Though VCE has become the preferred first-line method for luminal small bowel evaluation, it is limited by its inability to provide a tissue diagnosis [1,3,8,10].…”
Section: Introductionmentioning
confidence: 99%